Review: Investigation of the electrochemical properties of beta blockers and ACE inhibitors by cyclic voltammetry - Edhem Hasković; Ena Deljkić (Zaštita Materijala)
Hypertension is the most common cardiovascular disease in developed and developing countries, affecting about 20-30% of the adult population. It is an independent risk factor for cardiovascular disease and is associated with an increased incidence of stroke and coronary heart disease. Several types of antihypertensive drugs are used worldwide to control risk factors. Perindorpil is one of the medicines used to treat high blood pressure, heart failure or stable coronary artery disease. Metoprolol is a cardioselective beta1-adrenergic receptor blocker in the heart. They block the effect of adrenaline and noradrenaline on beta-adrenergic receptors in the body. Previous scientific research in the field of electrochemistry has enabled the development of sensitive, reliable and cheaper instruments that have significant contributions in the field of drug development and analysis. Cyclic voltammetry examines the activity of the drug itself, the effect of concentrations as well as the influence of different scan rates. We conclude that with an increase in the concentration of both Perindopril and Metoprolol, an increase in the current peak in the area of reduction is observed.